Ethical exchanges in translation, adaptation and dramaturgy - O'Toole, Emer; Kristić, Andrea Pelegri; Young, Stuart, 1958- (Themes in theatre ;, 2017)
Ethical Exchanges in Translation, Adaptation and Dramaturgy examines compelling ethical issues that concern practitioners and scholars in the fields of translation, adaptation and dramaturgy. Its 11 essays, written by academic theorists as well as scholar-practitioners, represent a rich diversity of philosophies and perspectives, and reflect a broad international frame of reference: Asia, Europe, North America, and Australasia. They also traverse a wide range of theatrical forms: classic and contemporary playwrights from Shakespeare to Ibsen, immersive and interactive theatre, verbatim theatre, devised and community theatre, and postdramatic theatre. In examining the ethics of specific artistic practices, the book highlights the significant continuities between translation, adaptation, and dramaturgy; it considers the ethics of spectatorship; and it identifies the tightly interwoven relationship between ethics and politics.